(untitled) (Al-Qamar, 2021)
This article discusses the religious trends of selected twentieth century women Urdu fiction writers. Focusing on Akhtar Jamāl, Jilānī Bāno, Qurratulain Hayder, Hājra Masroor, Khadīja Mastoor, Bāno Qudsia, Khālida Hussain, Jamīla Hāshmī, Sāira Hāshmī, it explores that firm belief in Allah Almighty, respect for humanity, moral values ​​and deference for women are prominent subjects in these women’s fictions. They have deep spiritual experiences of realities of life and Universe. Not only spiritual and esoteric observations, but conditions associated with them are skillfully described in their fictions. These writers have developed Islamic propensity in the genre of Urdu fiction, by writing comprehensively on a number of themes related to Islamic ideology.